Aerosol optical characteristics and their vertical distributions under enhanced haze pollution events: effect of the regional transport of different aerosol types over eastern China - T. Sun; H. Che; B. Qi; Y. Wang; Y. Dong; X. Xia; X. Xia; H. Wang; K. Gui; Y. Zheng; H. Zhao; Q. Ma; et al. (Atmospheric Chemistry and Physics, 2018)
The climatological variation of aerosol properties and the planetary boundary layer (PBL) during 2013–2015 over the Yangtze River Delta (YRD) region were investigated by employing ground-based Micro Pulse Lidar (MPL) and CE-318 sun-photometer observations. Combining Moderate Resolution Imaging Spectroradiometer (MODIS) and Cloud-Aerosol Lidar and Infrared Pathfinder Satellite Observation (CALIPSO) satellite products, enhanced haze pollution events affected by different types of aerosol over the YRD region were analyzed through vertical structures, spatial distributions, backward trajectories, and the potential source contribution function (PSCF) model. The results show that aerosols in the YRD are dominated by fine-mode particles, except in March. The aerosol optical depth (AOD) in June and September is higher due to high single scattering albedo (SSA) from hygroscopic growth, but it is lower in July and August due to wet deposition from precipitation. The PBL height (PBLH) is greater (means ranging from 1.23 to 1.84 km) and more variable in the warmer months of March to August, due to the stronger diurnal cycle and exchange of heat. Northern fine-mode pollutants are brought to the YRD at a height of 1.5 km. The SSA increases, blocking the radiation to the surface, and cooling the surface, thereby weakening turbulence, lowering the PBL, and in turn accelerating the accumulation of pollutants, creating a feedback to the cooling effect. Originated from the deserts in Xinjiang and Inner Mongolia, long-range transported dust masses are seen at heights of about 2 km over the YRD region with an SSA440 nm below 0.84, which heat air and raise the PBL, accelerating the diffusion of dust particles. Regional transport from biomass-burning spots to the south of the YRD region bring mixed aerosol particles at a height below 1.5 km, resulting in an SSA440 nm below 0.89. During the winter, the accumulation of the local emission layer is facilitated by stable weather conditions, staying within the PBL even below 0.5 km.